Properties of Cement Brick with Partial Replacement of Sand and Cement with Oil Palm Empty Fruit Bunches and Silica Fume - Jen Hua Ling; Yong Tat Lim; Wen Kam Leong; Euniza Jusli; How Teck Sia (Journal of the Civil Engineering Forum, 2019)
Oil palm empty fruit bunches (EFB) and silica fume (SF) are the by-products of the oil palm plantation and the ferroalloy smelting industries, respectively. Improper disposal of these materials leads to negative implication to the environment. This study was carried out to investigate the potential application of EFB and SF in cement bricks. EFB fibre and SF replaced up to 25% of sand and cement in the mix, respectively, in several groups of specimens that distinguished the normal, EFB-, SF- and EFB-SF-cement bricks. The specimens were tested for the compressive strength, density and water absorption property. The results reveal that SF, at an optimum amount of 10% cement replacement, increased 10% of the strength of the cement brick. EFB fibre reduced the strength and density but increased water absorption property of the cement brick. For application in the construction industry, SF and EFB fibre contents should be kept within 10% and 20% respectively.